PELASANAAN NILAI-NILAI MURNI MENGIKUT SISTEM PENGURUSAN KUALITI (SPK) BERASASKAN PIAWAIAN SYARIAH (MS 1900:2014) TERHADAP KEPUASAN BEKERJA DALAM KALANGAN KAKITANGAN UNIVERSITI - Azmi Ahmad (Tesis, 2020)
This study was conducted to identify the level of understanding, inculcation and application of core values according to the Shari'ah -Based Quality Management System (QMS) (MS1900:2014) in a certified instituion of higher learning, besides to study the relationship between the core values and job satisfaction.